o-nt=h+z

Multiply each term in o-nt=h+z by t.

o-nt⋅t=h⋅t+z⋅t

Cancel the common factor of t.

Cancel the common factor.

o-nt⋅t=h⋅t+z⋅t

Rewrite the expression.

o-n=h⋅t+z⋅t

o-n=h⋅t+z⋅t

Multiply z by t.

o-n=ht+zt

o-n=ht+zt

Rewrite the equation as ht+zt=o-n.

ht+zt=o-n

Factor t out of ht.

th+zt=o-n

Factor t out of zt.

th+tz=o-n

Factor t out of th+tz.

t(h+z)=o-n

t(h+z)=o-n

Divide each term in t(h+z)=o-n by h+z.

t(h+z)h+z=o-nh+z

Cancel the common factor of h+z.

Cancel the common factor.

t(h+z)h+z=o-nh+z

Divide t by 1.

t=o-nh+z

t=o-nh+z

t=o-nh+z

Solve for t ( square root of o-n)/t=h+z